DAMPAK AKUMULASI MODAL, EKSPOR, MARGINAL EFFICIENCY OF CAPITAL (MEC), INFLASI DAN SISTEM PEMERINTAHAN TERHADAP PERTUMBUHAN EKONOMI - Asti Karlina Dewi (Lembaga Penerbit Fakultas Ekonomi dan Bisnis, 2017)
The research is analyzing the Impact of Capital Acumulation, Export, MEC, Inflation and Governace System on Indonesian Economic Growth. The model tries to combine the supply side (capital accumulation and MEC) and the demand side (export and inflation), also by including government systems for predicting the factors affecting economic growth. The data used are secondary data obtained from BPS, BI and other data sources from 1987 to 2016 (except data from 1998, 1999, and 2000 due to data in that year's is extreme). To find out whether there is a difference in the phenomenon of economic growth in centralized systems with decentralize system used dummy variables. The results of the study showed that the model is significant in explaining changes in economic growth. The impact of capital accumulation on economic growth is positive significant, as well as the impact of exports. But the impact of MEC as well as of inflation on economic growth is not significant. By seeing that the variable dummy has a significant positive impact on economic growth, it can be argued that economic growth in the decentralized system is better than the centralized.